2005
DOI: 10.1021/ma050040t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Weight Distribution on Microphase-Separated Structures from Block Copolymers

Abstract: The effect of molecular weight distribution on microphase-separated structures for both AB diblock and BAB triblock copolymers was investigated in comparison with that of composition distribution. Monodisperse poly(styrene-b-2-vinylpyridine) (SP) and poly(2-vinylpyridine-b-styrene-b-2vinylpyridine) (PSP) parent block copolymers were synthesized by living anionic polymerizations whose volume ratios were all designed to be 0.5/0.5. Three parent copolymers were blended variously with both number-average molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 39 publications
4
89
0
Order By: Relevance
“…Listak et al 42 recently reported that polydispersity stabilized a hexagonally perforated lamellar mesostructure in poly͑styrene-b-methyl acrylate͒ diblock copolymers; this structure is considered metastable in nearly monodisperse materials. 45,46 Polydispersity may also induce macrophase separation into multiple coexisting morphologies, 22,25,30 as reported in homopolymer/ polydisperse diblock 10 and multicomponent diblock/diblock blends, [35][36][37] and as predicted for some polydisperse materials with continuous molecular weight distributions ͑MWDs͒.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Listak et al 42 recently reported that polydispersity stabilized a hexagonally perforated lamellar mesostructure in poly͑styrene-b-methyl acrylate͒ diblock copolymers; this structure is considered metastable in nearly monodisperse materials. 45,46 Polydispersity may also induce macrophase separation into multiple coexisting morphologies, 22,25,30 as reported in homopolymer/ polydisperse diblock 10 and multicomponent diblock/diblock blends, [35][36][37] and as predicted for some polydisperse materials with continuous molecular weight distributions ͑MWDs͒.…”
Section: Introductionmentioning
confidence: 80%
“…A flurry of theoretical [25][26][27][28][29][30][31][32][33][34] and a͒ Authors to whom correspondence should be addressed: Electronic addresses: hillmyer@umn.edu and bates@cems.umn.edu. experimental 11,27,[35][36][37][38][39][40][41][42][43] studies of polydispersity effects in AB block copolymers followed Bendejacq et al's report. This topic recently has been reviewed, 44 and only a brief summary is provided below.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The previous morphological observation for polydisperse block copolymers in composition and molecular weight clarified that lamellar domain spacing increases linearly with increasing the polydispersity in molecular weight or composition. [25][26][27] However, these results suggested only speculation on spatial distribution of the component block chains in microdomains. Thus, the segmental distribution of the component chains in block copolymer blends was directly examined by neutron reflectometry.…”
Section: Localization Of Component Chains In a Block Copolymer Blend mentioning
confidence: 87%
“…The evaluated segmental distribution in the block copolymer blend supported the previous morphological observations well. [25][26][27] Interdiffusion Behavior of a Cyclic Polystyrene Compared with a Linear Homologue A cyclic polymer has attracted much attention from the aspects of polymer physics due to its unique feature in molecular architecture with no chain ends. The existence of chain ends is essential for polymer dynamics such as diffusion and relaxation of a linear polymer chain in melt in the context of reptation theories.…”
Section: Localization Of Component Chains In a Block Copolymer Blend mentioning
confidence: 99%